Impaired burrowing is the most prominent behavioral deficit of aging htau mice - Geiszler, Philippine C.; Barron, Matthew; Pardon, Marie-Christine (Elsevier, 2016)
htau mice are deficient of murine tau but express all six human tau isoforms, leading to gradual tau misprocessing and aggregation in brain areas relevant to Alzheimer's disease. Whilst histopathological changes in htau mice have been researched in the past, we focused here on functional consequences of human tau accumulation. htau mice and their background controls - murine tau knock-out (mtau-/-) and C57Bl/6J mice - underwent a comprehensive trial battery to investigate species-specific behaviour, locomotor activity, emotional responses, exploratory traits, spatial and recognition memory as well as acquisition, retention and extinction of contextual fear at two-, four-, six-, nine- and twelve-months-of-age. In htau mice, tau pathology was already present at two-months-of-age, whereas deficits in food burrowing and spatial working memory were first noted at four-months-of-age. At later stages the presence of human tau on a murine tau knockout background appeared to guard cognitive performance; as mtau-/- but not htau mice differed from C57Bl/6J mice in the food burrowing, spontaneous alternation and object discrimination tasks. Aging mtau-/- mice also exhibited increased body mass and locomotor activity. This data highlights that reduced food burrowing performance was the most robust aspect of the htau phenotype with ageing. htau and mtau-/-deficits in food burrowing pointed at the necessity of intact tau systems for daily life activities. Whilst some htau and mtau-/- deficits overlap, age differences between the two genotypes may reflect distinct functional effects and compared to C57Bl/6J mice, the htau phenotype appeared stronger than the mtau-/- phenotype at young ages but milder with ageing.